Effect of Pineapple Peel Probiotics in Drinking Water on The Production Performance and Egg Quality of Quail - Lestari, Retno Budi; Permadi, Edy; Andri, Andri; Tribudi, Yuli Arif; Mustaqim, Zainul (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
This study aimed to evaluate the effects of adding pineapple peel probiotics to drinking water on quail productivity and egg quality. The experiment used 240 Peksi strain quails, aged 12 weeks, and pineapple peel probiotics containing Lactobacillus casei. A completely randomized design was applied, with six treatment groups receiving varying concentrations of pineapple peel probiotics in drinking water: 0% (P0), 1%/liter (P1), 2%/liter (P2), 3%/liter (P3), 4%/liter (P4), and 5%/liter (P5). The observed parameters included feed consumption, hen-day production (HDP), egg weight, feed conversion ratio, and the fat and cholesterol content of the eggs. Data were analyzed using ANOVA, followed by Duncan's test for post-hoc comparisons where significant differences were observed. The addition of pineapple peel probiotics in drinking water did not significantly affect (P>0.05) feed consumption, daily egg production, egg weight, feed conversion ratio, or the fat and cholesterol content of the eggs. However, supplementation at pineapple peel probiotics in drinking water to can daily egg production in quails.